Variáveis familiares de crianças com deficiência e os tipos de escolarização inclusiva e segregada - Gualda, Danielli Silva (2015)
This study aimed to: (a) Describing and comparing the family-school relationship in the parents or guardians opinion for preschool children with disability, enrolled in regular schools, in special schools and, also, of those parents whose children have experienced both types of schooling; (b) Describing and comparing the needs, resources and social support of the families of three groups of parents or guardians of preschool children with disabilities, in accordance with the different types of education and (c) relating familyschool relationship, resources, needs and social support of parents or guardians of preschool children with disability. Attended of the research 55 parents or guardians of children with disability, 20 had the children enrolled in regular education pre-schools (GEC), 15 had the children enrolled only in special schools (GIE) and 20 had the children enrolled in both schools (GA). Data collection occurred in 34 municipal preschools and 2 special schools. To fulfill the targets, the parents responded in the form of interview, 6 instruments: Brazil Criteria questionnaire; questionnaire about the family-school relationship in the process of inclusion (version for parents); Checklist of shared routine and involvement between family-school version for parents (mom, dad or guardian); Inventory of the family environment resources (FER); Questionnaire about the needs of families (QNF); and about social support questionnaire (SSQ). Qualitative data were analyzed by means of categories, with the participation two judges. Quantitative data analyzed using descriptive methods central tendencies and dispersion measures. It was used ANOVA ad Chi-square test to compare the groups. Correlation test was used for Pearson to relate the variables. Regarding the first objective, the results showed that families who have children enrolled in regular school (GEC and GA) went to school more often without being convened, while they also spoke more frequently different topics with the teacher, when compared with the GIE and GA. As for the second objective, it was possible to note that most of children of the three groups had a well-stimulating family environment, as well as the resources within this context, the developed interactions with the family members and the variety of developed activities by parents with these children. Regarding the social support, in general, the GEC families had a higher satisfaction with social support received, compared with the GA families. Finally the third goal made some significant correlations, such as: family-school relationship showed positive correlations with the fact that the child has the routine to perform the daily activities and to have moments of family meetings. The needs related to information , support , explain to others , community services , financial and the functioning of family life , also correlated positively with the right hour that the child had to perform the activities of daily life.